2000
DOI: 10.1104/pp.124.4.1582
|View full text |Cite
|
Sign up to set email alerts
|

A New Set of Arabidopsis Expressed Sequence Tags from Developing Seeds. The Metabolic Pathway from Carbohydrates to Seed Oil,

Abstract: Large-scale single-pass sequencing of cDNAs from different plants has provided an extensive reservoir for the cloning of genes, the evaluation of tissue-specific gene expression, markers for map-based cloning, and the annotation of genomic sequences. Although as of January 2000 GenBank contained over 220,000 entries of expressed sequence tags (ESTs) from plants, most publicly available plant ESTs are derived from vegetative tissues and relatively few ESTs are specifically derived from developing seeds. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
174
1
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(189 citation statements)
references
References 41 publications
8
174
1
2
Order By: Relevance
“…Our analysis revealed that three of the eight potential transcripts (At4g28520.1, At5g44120.3 and At1g3880.1) gave rise to the bulk of the cruciferin protein in seeds. The contribution from At1g3890.1 was much smaller, which is in keeping with the low abundance of this transcript [32]. The At4g28520.2 and At4g28520.3 transcripts encode proteins with internal deletions; however, tryptic peptides capable of distinguishing these variants from At4g28520.1 were not detected.…”
Section: Expression and Heterogeneity Of Cruciferinmentioning
confidence: 55%
See 1 more Smart Citation
“…Our analysis revealed that three of the eight potential transcripts (At4g28520.1, At5g44120.3 and At1g3880.1) gave rise to the bulk of the cruciferin protein in seeds. The contribution from At1g3890.1 was much smaller, which is in keeping with the low abundance of this transcript [32]. The At4g28520.2 and At4g28520.3 transcripts encode proteins with internal deletions; however, tryptic peptides capable of distinguishing these variants from At4g28520.1 were not detected.…”
Section: Expression and Heterogeneity Of Cruciferinmentioning
confidence: 55%
“…Columbia genome contains four loci that encode cruciferins: At5g44120 [CRA1 (cruciferin precursor)], At1g03880 [CRB (cruciferin B)], At4g28520 [CRC (cruciferin C)] and At1g03890 (putative cruciferin) [10]. The majority of the transcripts arise from At4g28520, At5g44120 and, to a lesser extent, from At1g03880 [32]. At1g03890 is located in tandem with the locus encoding CRB and was once believed to be a pseudogene; however, a cDNA has recently been assigned to it (http://signal.salk.edu/).…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, the Y2001 AFGC DNA microarrays contained 11,300 Arabidopsis EST clones collected from public sources (Newman et al, 1994;White et al, 2000) and 3,000 gene-specific fragments amplified from genomic DNA. As controls, Arabidopsis clones for genes with constant high (n ϭ 3), medium (n ϭ 3), and low (n ϭ 3) expression levels were distributed evenly on the slide.…”
Section: Microarray Preparationmentioning
confidence: 99%
“…Metabolically specialised enzymes pertaining to oil biosynthesis in J. curcas can be identified easily through EST sequencing of cDNAs prepared from seeds because mRNA clones corresponding to these enzymes could be relatively abundant. Large scale single-pass sequencing of cDNAs from different plants has provided a large repository of genes whose tissuespecific expression can be evaluated for the cloning of genes in addition to the development of markers for map-based cloning (White et al 2000). In J. curcas, volumes of genomic data that include the whole genome (Sato et al 2011) and seed transcriptome information have been generated in the last few years (King et al 2011).…”
Section: Introductionmentioning
confidence: 99%